Roles of gate-oxide thickness reduction in scaling bulk and thin-body tunnel field-effect transistors - Chien, Nguyen Dang; Anh, Dao Thi Kim; Shih, Chun-Hsing (Vietnam Journal of Science and Technology, 2017)
Tunnel field-effect transistor (TFET) has recently been considered as a promising candidate for low-power integrated circuits. In this paper, we present an adequate examination on the roles of gate-oxide thickness reduction in scaling bulk and thin-body TFETs. It is shown that the short-channel performance of TFETs has to be characterized by both the off-current and the subthreshold swing because their physical origins are completely different. The reduction of gate-oxide thickness plays an important role in maintaining low subthreshold swing whereas it shows a less role in suppressing off-state leakage in short-channel TFETs with bulk and thin-body structures. When scaling the gate-oxide thickness, the short-channel effect is suppressed more effectively in thin-body TFETs than in bulk devices. Clearly understanding the roles of scaling gate-oxide thickness is necessary in designing advanced scaled TFET devices